Manifest, Latent, and Dysfunctional Roles of Tuha Peut in Family Conflict Resolution: A Case Study from Gampong Reudeup, Aceh, Indonesia - Nusuary, Firdaus Mirza; Zikriah, Zikriah (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study investigates the role of Tuha Peut in resolving family conflicts in Gampong Reudeup, Panteraja Subdistrict, Pidie Jaya District, within the framework of Robert K. Merton’s structural-functional theory. As a customary institution at the village level, Tuha Peut is formally mandated to maintain social order through deliberation, mediation, and legal oversight. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and document analysis. Thematic analysis was conducted to identify the manifest, latent, and dysfunctional roles of Tuha Peut in conflict resolution. The findings reveal that Tuha Peut performs manifest functions as a mediator and decision-maker in resolving domestic disputes, while its latent functions include reinforcing communal values and informal cohesion mechanisms. However, the study also identifies structural dysfunctions, particularly related to gender representation. Several female informants expressed discomfort engaging with Tuha Peut directly, often relying instead on informal female figures such as Ibu Ros to mediate access. This phenomenon suggests a gap between formal institutional structures and the lived experiences of community members. The study concludes that while Tuha Peut contributes significantly to social stability, its legitimacy and effectiveness are contingent upon its capacity to evolve. Institutional reforms—especially gender inclusion and the recognition of informal mediators—are essential to ensuring that Tuha Peut fulfills not only its legal mandate but also its social responsibilities in an inclusive and representative manner.